Preanalytical Stability of CSF Total and Oligomeric Alpha-Synuclein - Abdi, Ilham Y.; Majbour, Nour K.; Willemse, Eline A. J.; van de Berg, Wilma D. J.; Mollenhauer, Brit; Teunissen, Charlotte E.; El-Agnaf, Omar M. (Frontiers in Aging Neuroscience, 2021)
Background: The role of cerebrospinal fluid (CSF) alpha-synuclein as a potential biomarker has been challenged mainly due to variable preanalytical measures between laboratories. To evaluate the impact of the preanalytical factors contributing to such variability, the different subforms of alpha-synuclein need to be studied individually. Method: We investigated the effect of exposing CSF samples to several preanalytical sources of variability: (1) different polypropylene (PP) storage tubes; (2) use of non-ionic detergents; (3) multiple tube transfers; (4) multiple freeze-thaw cycles; and (5) delayed storage. CSF oligomeric- and total-alpha-synuclein levels were estimated using our in-house sandwich-based enzyme-linked immunosorbent assays. Results: Siliconized tubes provided the optimal preservation of CSF alpha-synuclein proteins among other tested polypropylene tubes. The use of tween-20 detergent significantly improved the recovery of oligomeric-alpha-synuclein, while multiple freeze-thaw cycles significantly lowered oligomeric-alpha-synuclein in CSF. Interestingly, oligomeric-alpha-synuclein levels remained relatively stable over multiple tube transfers and upon delayed storage. Conclusion: Our study showed for the first-time distinct impact of preanalytical factors on the different forms of CSF alpha-synuclein. These findings highlight the need for special considerations for the different forms of alpha-synuclein during CSF samples’ collection and processing.